Yet Another Challenge for the Automotive Software: Deep Learning - Falcini, Fabio; Lami, Giuseppe; Mitidieri, Alessandra (IEEE software, 2017)
In automotive software, the deep learning-based systems, with their peculiar features, are playing an increasingly pervasive role. As a result, inside the automotive software engineering community, an awareness of the need of integrating the deep learning development approach with the "traditional" ones is growing, at technical, methodological and cultural levels. In particular, the innovative and data-intensive phase of deep neural network training, by means of ad-hoc training data, is pivotal in the software development of vehicle functions that rely on such a technology paradigm and thus necessitates a special focus. A development lifecycle fitting deep learning needs is introduced and an improvement initiative, based on Automotive SPICE, for an effective adoption of DNN in the automotive software applications is presented.